The transition of enhancing financial performance in the mining and agriculture sector - Leo Cahya Trias Putra Rachman; Muhammad Firdaus; Bunasor Sanim (Jurnal Keuangan dan Perbankan, 2019)
In times of crisis, a decline in company performance can potentially be the cause of bankruptcy. The study of financial distress and turnaround has a close relationship, because the successful turnaround is determined from efforts to overcome the company's problems with financial distress. The purpose of this study is to analyze the factors that significantly influence the transition of financial performance and also to formulate managerial implications related to the success of turnaround in mining and agriculture sub-sector companies. The logistic regression method (logit) is used to discriminate samples of companies with the distressed category and also the turnaround category. The results of the study show that the transition of the company's financial performance is influenced by the variables of company size, level of distress and industry type. Alternative strategies that have been formulated consist of efficiency and entrepreneurial oriented strategies. Based on studies that have been conducted, the agricultural sector has a better probability of transition than the mining sector.JEL Classification: C01, C58, G01, G33DOI: https://doi.org/10.26905/jkdp.v23i3.2755